Experimental investigation of combustion characteristics under different ventilation conditions in a compartment connected to a stairwell. (25th May 2016) - Ji, J.; Li, M.; Gao, Z.H.; Li, Y.F.; Shi, W.X.; Sun, J.H.
Highlights: A set of burning experiments was conducted in an under-ventilated stairwell. Flame behaviors are different with vents opened on the 1st floor and higher floor. θ and η can be roughly used to identify whether the fire is ventilation control. The degree of under-ventilated increases with the opening height and pool size. β with turbulent mixing is compared with previous studies of stack effect. Abstract: A set of experiments was conducted in a scaled building model with 12 floors to study the effect of different ventilation conditions on combustion characteristics in a compartment connected to a stairwell with single opening. The results show that when the opening was set at the 1st floor, the upper part of thermal plume inclined to doorway while the lower part inclined to the opposite direction, like a crescent. A special phenomenon, ghosting flame, took place in the experiments where the fire source was relatively large and the opening was set at the 3 rd, 6 th, and 9 th floors, which was considered to be a result of insufficient oxygen supply. The mass loss rate in the current work decreased after the occurrence of ghosting flames. Two parameters θ, which is related to fuel mass loss rate, and η, which is related to the air flow rate at the opening of the stairwell, can be roughly used to identify whether the fire is ventilation control. It is shown that θ increases with the opening height and pool size. The ghosting flames appear at a large degree of under-ventilated condition. There was a stable neutral plane at the opening at the 1 st floor, whereas no stable neutral plane was identified at the openings at higher floors. Smoke moving upward depends on turbulent mixing in the stairwell in the current work. Temperature attenuation coefficient with the movement mechanism of turbulent mixing is much higher than that with the movement mechanism of stack effect.